Blogs de personagens de telenovelas: convergências entre o real e o ficcional - Souza, José Glaydson Pereira de (2014)
The convergence culture has led to significant changes in the forms of production and consumption of fictional narratives. In this context, the blogs of characters emerge as one of the forms of narratives that lead transmídias the fictional TV content into cyberspace. Thus, it is important to analyze the configuration of this new communications ambience involving fictional narratives and not fictional, character and surfer, as well as the relationship that builds between them. Thus, this dissertation is to investigate general purpose, in the process of transmediação of soap operas for internet, similarities between the fictional and the real. We selected as the unit of analysis Blog Indra, the soap opera “Caminho das Índias” (Passage to Indias) (Rede Globo, 2009). The specific research objectives were: to analyze, from blog posts as they are constructed identity of the character and the identity profile of the public; identify the forms of sociality explored at the blog for the relationship characters/public and investigate how these forms of sociality promote convergences between presential and fictional world. The research, qualitative and interpretative nature, was conducted in two stages. At first, with reference to the concept of “Communication Contract” (CHARADEAU 2006, 2012), we did a descriptive and discursive approach to the blog, in which we demonstrate how the television narrative, blog, articulates the fictional and non-fictional. In the second step, we seek to understand the forms of sociality involved in the blo g, from the notions of presenteism (emphasis on everyday), ethics, aesthetics (sense of belonging) and tribalism (IDs). In this direction, we seek theoretical support in the comprehensive sociology of Michel Meffesoli (MAFESOLLI, 2007, 2010). The analysis of the posts in the first phase showed us that the identity of the character becomes Indra from discursive strategies that "simulate" the existence of a "blogger real world", being the identity profile of the Internet audience designed according to this perspective. The second step of the analysis showed that the identification of Internet users with the character extends to the "everyday" presented on the blog, thus indicating that the public creates links with the fictional: also sharing their stories, their feelings and affinities. Accordingly, we conclude that sociality is a majo r factor on the similarities between the fictional and the real of transmedia narratives.